Effects of mass transfer and MHD Casson nanofluid heat transfer on thermophoresis at stagnation point - V. Seethamahalakshmi; U. Venkata Kalyani; A. Padma; P.S.S. Nagalakshmi; G.V. Ramana Reddy; Charankumar Ganteda; Vediyappan Govindan; Haewon Byeon; Seepana Praveenkumar; Busayamas Pimpunchat (Case Studies in Thermal Engineering)
This study seeks to analyse the magnetohydrodynamic (MHD) flow of a nanofluid, focussing on heat and mass transfer in nano liquids over a stretchable surface near a stagnation point, while considering changeable thermal conductivity. The thermal behavior of the suspended nanoparticles is found to be significantly affected by Brownian motion. The influence of the chemical responses well as the continuous inner warmth source or washbasin are in addition taken into account. The governing equations are changed into a system of coupled ordinary differential equations utilising an appropriate similarity transformation. The computational software PYTHON is employed to address the boundary value problem (BVP) utilising the shooting method. The numerical results are supported by the online PYTHON software function bvp4c. The numerical results are derived by varying the values of the physical parameters associated with the flow problem. The results are presented in graphical and tabular formats. As the thermal energy of the liquid increases, the thermophoresis values trend upward, while the Nb values show a downward trajectory. Also, we found that the response rate encourages a reduction in the thermal boundary layer's thickness.